Unintended effects of targeted advertisements : a test on Sarawakian Chinese / Ernest Cyril De Run - De Run, Ernest Cyril (Faculty of Business and Management ; UiTM Press, 2007)
The purpose of targeted advertising is to transmit a message from a sender directly to an intended, pre-chosen, and segmented audience who should prefer the targeted communication and respond favorably towards it. However, there is always the potential for other non-targeted groups to view the advertisement. Unintended consequences such as negative attitudinal, emotional, and behavioral reactions may occur. This article tests these effects based on relevant theories in the communication and advertising literature on a distinct nondominant ethnic group (Chinese) in Sarawak, Malaysia. The study utilizes questionnaires based on a fictitious advertisement. The findings suggest that there are negative attitudinal, emotional, and behavioral reactions by those not targeted who see these advertisements.